O contributo da proteção catódica na prevenção da degradação nas estruturas internas em ferro das esculturas em gesso : da reserva de escultura da Faculdade de Belas-Artes da Universidade de Lisboa - Souza, Oséias Carneiro de (2022)
This Project Work, developed within the scope of the Masters in Conservation Sciences, Restoration and Production of Contemporary Art, at the Faculty of Fine Arts of the University of Lisbon, has as its main objective to find a solution for the problems caused by the deterioration of internal iron structures in plaster cast sculptures. The project was developed to obtain real and simple data in the research of a methodology for the area of plaster work conservation, through the contribution of cathodic protection by sacrificial anodes, which was applied first in laboratory tests and later in three cases of study belonging to the plaster cast collection of the faculty. The Cathodic protection is obtained when the electrochemical principles of metals in an electrolyte are applied, it consists of the protection of metal surfaces against corrosion through the application of anodes that support corrosion. It is currently used by the materials engineering sector on structures that are buried or submerged, on reinforced concrete, masonry structures, buildings, among others. However, the use in works of art has been barely or not explored, especially in plaster cast sculptures with internal iron structures. In this project, the studies were carried out on cathodic protection, on iron, on plaster, on the techniques involved for the internal structures of the sculptures, and the mechanisms of degradation of materials, which were essential for the test’s elaboration. The laboratory tests were carried out on forty-two specimens, with different dimensions and different installations of the anodes in a period of 192 days between March and October. The results with the specimens with zinc anode number 02, 03, 04 and 08 allowed the obtention of essential and effective data for the methodology used in the intervention of the three case studies, in a real and safe way. This methodology allowed, on the intervention of the case studies, the stabilization of the iron’s structure without altering its material. In this sense, the contribution of cathodic protection innovates with the prevention of corrosion to safeguard the plaster heritage.